Therapeutic angiogenesis for cardiovascular disease - Ng, Yin-Shan (BioMed Central, 2001)
The identification of angiogenic growth factors, such as vascular endothelial growth factor and fibroblast growth factor, has fueled interest in using such factors to induce therapeutic angiogenesis. The results of numerous animal studies and clinical trials have offered promise for new treatment strategies for various ischemic diseases. Increased understanding of the cellular and molecular biology of vessel growth has, however, prompted investigators and clinicians alike to reconsider the complexity of therapeutic angiogenesis. The realization that formation of a stable vessel is a complex, multistep process may provide useful insights into the design of the next generation of angiogenesis therapy.